Developing a conceptual Shari’ah framework of Green Sukuk for Bangladesh: its implications on social welfare by realizing SDGs - Habibullah, Mohammad; Hassan, Rusni (IIUM Press, 2023)
As a Shari’ah-compliant Islamic bond, Sukuk has attracted much interest from all over the world, particularly in Muslim countries like Bangladesh. Previous studies have confirmed that compared to interest-based bonds, Sukuk based on profitsharing contracts is much more beneficial for investors. Specifically, in a Muslim-majority country like Bangladesh, Sukuk can attract much more interest because the existing capital market of this country severely lack Shari’ah compliant instruments. The goal of this study is to introduce a Shari’ah-based conceptual framework of Green Sukuk that will be specifically applicable in Bangladesh considering the socio-economic conditions of the common people and the existing legal and regulatory framework of the country. In achieving this objective, a systematic literature review approach is adopted in this study. While creating the Shari’ah framework of Sukuk, importance has been given to Maqasid-al-Shari’ah and the sustainable development goals (SDGs). Emphasis has also been given on ensuring poverty alleviation and the social and economic welfare of people by highlighting the notion of hifz-al-maal (preservation of wealth) and hifz-al-deen (preservation of faith). It is expected that the new Green Sukuk model, once implemented in Bangladesh, will contribute towards achieving the SDGs, which require an unprecedented number of resources to be mobilized.